SIFAT FISIK DAN KEKUATAN MEKANIK KAYU AKASIA MANGIUM (Acacia mangium Willd) DARI HUTAN TANAMAN INDUSTRI KALIMANTAN SELATAN - Arsad, Effendi (Jurnal Riset Industri Hasil Hutan, 2011)
Acacia Mangium wood can to used for substitution comercial wood. Materiel Acacia mangium woods  was take from HTI at  seven age with diameter   30 – 33 cm.   The results Physical properties and mechanical strength obtained by the water content of dry air from 13.78 to 14.89%; density of 0.60 to 0.62 gr/cm3; specific gravity of 0.59 to 0.61; compressive strength parallel fibers from 319.54 to 361.70 Kg/cm2; compressive strength perpendicular to fiber 117-197 kg/cm2; bending strength (MOR) from 509.25 to 680.50 kg/cm2; cleave strength 80.25 to 110.90 kg/cm2; tensile strength of 98.27 to  133.03 kg/cm2; shear strength of parallel fiber from 93.53 to 149.43 kg/cm2 and hardness from 453 to 565 kg/cm2.  Physical properties and mechanical  strenght  can was  standard  for furniture and  construction.Keywords: acacia mangium wood, physical  and mechanical  wood